(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This in the thesis corporate finance of the field central from problems one is capital structure optimization issue theoretical point of view from the point of view analysis Traditional from the approach pull modern market time to theory was seven main theoretical approach seeing out , their essence , main postulates and mutual differences open Research results this shows that no one theory capital structure formation all aspects complete explain can’t , that’s it because of in practice integrated approach application to the goal is appropriate